2012
DOI: 10.1016/j.bmc.2011.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Mefloquine–oxazolidine derivatives, derived from mefloquine and arenecarbaldehydes: In vitro activity including against the multidrug-resistant tuberculosis strain T113

Abstract: Ten new mefloquine-oxazolidine derivatives, 4-[(1S,8aR)-3-(aryl)hexahydro[1,3]oxazolo[3,4-a]pyridin-1-yl]-2,8-bis(trifluoromethyl)quinoline (1: aryl=substituted phenyl) and 4-[(1S,8aR)-3-(heteroaryl)hexahydro[1,3]oxazolo[3,4-a]pyridin-1-yl]-2,8-bis(trifluoromethyl)quinoline [2: heteroaryl=5-nitrothien-2-yl (2a); 5-nitrofuran-2-yl (2b) and 4H-imidazol-2-yl) (2c)], have been synthesized and evaluated against Mycobacterium tuberculosis. Compounds 1f (aryl=3-ethoxyphenyl), 1g (Ar=3,4,5-(MeO)(3)-C(6)H(2)) and 2c we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…GONÇALVES et al [4] showed that mefloquine-oxazolidine derivates have in vitro activity against M. tuberculosis. In addition, mefloquine can inhibit the Mycobacteria species in a MIC range of 8-16 µg·mL…”
Section: Mefloquine As a Potential Drug Against Multidrug-resistant Tmentioning
confidence: 99%
“…GONÇALVES et al [4] showed that mefloquine-oxazolidine derivates have in vitro activity against M. tuberculosis. In addition, mefloquine can inhibit the Mycobacteria species in a MIC range of 8-16 µg·mL…”
Section: Mefloquine As a Potential Drug Against Multidrug-resistant Tmentioning
confidence: 99%
“…The study showed that the electronic nature of substituents in the aryl ring plays a significant role on the antimycobacterial activity. Inhibitors having electronreleasing groups, such as hydroxy and methoxy groups, were more active than electron-withdrawing chloro or nitro groups 31,33 . Eswaran et al designed four new series of hydrazine-linkedquinolines based on the structure of mefloquine (Figure 8).…”
Section: Quinoline Derivatives Derived From Drugsmentioning
confidence: 99%
“…Moreover, several mefloquine derivatives have been reported to display modest to excellent actives against tuberculosis [14][15][16][17][18][19]. Among these derivatives is a series of mefloquine-oxazolidine derivatives, 2, [18,19], see Fig.…”
Section: Introductionmentioning
confidence: 98%
“…1. Certain of these derivatives, 2, especially those with electron releasing substituents, such as hydroxyl and alkoxyl groups, showed significant activity in in-vitro tests against the multidrug-resistant tuberculosis strain T113 [19]. However as (2: X ¼ H) and (2: X ¼ 4-F) also had reasonable activities as anti-TB agents, but not (2: X ¼ 2-F), (2: X ¼ 4-Cl) nor (2: X ¼ 4-Br), the activity data suggested that factors, other than the electronic effects of substituents, could also be important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation